Klastotė ant kortos: semiotika ir autentiškumo problema - Ousmanova, Almira (Problemos, 2004)
The essay provides a critical assessment of the debates concerning the concepts of fake and original (authentic) in the context of semiotics (Ch.S. Peirce, T. de Lauretis, U. Eco, M. Bal), philosophy (N. Goodman, J. Baudrillard, S. Žižek), art theory (W Benjamin, I. Haywood, N. Bryson), history (C. Ginzburg). It is an attempt to represent the problem of reproduction of cultural artefacts as a multifaceted issue which embraces the whole series of related notions (fake, forgery, imitation, reproduction, replication, remake, copy, pastiche, etc.) along with their different meanings and implications for various cultural practices (fine arts, history, architecture, cinema, social and cultural ‘apparatuses’ of identification). The main aim of the text is to provide an interdisciplinary frame of interpretation of the phenomenon of forgery, to reveal how aesthetic judgments on the originality (and aura) of the work of art are determined by economical and political factors and to show how the ’ideology of original’ is related to the power-knowledge system and the issues of political economy in contemporary Western culture. Semiotics (particularly, in U. Eco’s version) is chosen here as the most promising and efficient tool for the analysis of this complex phenomenon.